No Interaction, No Watching: Watching Characteristics of the Social Short Video Era. - Jiang, Zhiquan; Sun, Xiaocheng (Critical Arts: A South-North Journal of Cultural & Media Studies)
The current rapid development of social short videos on the Internet, which on the one hand satisfy people's needs for amusement and information in fragmented time and, on the other hand, have become a popular new social tool with their own characteristics. Compared to traditional social media, social short video watching includes real-time interactivity of pictures, personalised features, gamification, and the pursuit of the bizarre. Social short videos cater to human psychological enjoyment mechanisms, establish reward operation mechanisms, establish interaction guidance mechanisms, and employ big data and algorithm technology to govern the social watching process and its outcomes. As a real-time social tool with fast feedback, short videos do not solve the problems of social anxiety, social depth, and social efficiency, and their negative consequences, including information fragmentation and the "information cocoon", are further regulated.